Hydro-Acoustic and Hydrodynamic Optimization of a Marine Propeller Using Genetic Algorithm, Boundary Element Method, and FW-H Equations - Abouzar Ebrahimi; Mohammad Saeed Seif; Ali Nouri-Borujerdi (Journal of Marine Science and Engineering, 2019)
Noise generated by ships is one of the most significant noises in seas, and the propeller has a significant impact on the noise of ships, which reducing it can significantly lower the noise of vessels. In this study, a genetic algorithm was used to optimize the hydro-acoustic and hydrodynamic performance of propellers. The main objectives of this optimization were to reduce the propeller noise and increase its hydrodynamic efficiency. Modifying the propeller geometry is one of the most effective methods for optimizing a propeller performance. One of the numerical methods for calculating propeller noise is the Ffowcs Williams and Hawkings (FW-H) Model. A numerical code was developed by authors which solved these equations using the velocity and pressure distribution around the propeller and calculated its noise. To obtain flow quantities and to investigate the hydrodynamic performance of the propeller, a code was developed using a Boundary Element Method, the panel method. The geometry of DTMB 4119 propeller was selected for optimization, where geometric modifications included skew angle, rake angle, pitch to diameter (P/D) distribution, and chord to diameter (c/D) distribution. Finally, the results of geometric optimization were presented as Pareto optimal solutions. The results indicated that the optimum geometries had rake angles between 8.14 and 12.05 degrees and skew angles between 31.52 and 39.74 degrees. It was also observed that the increase in the chord up to a specific limit enhanced the efficiency and reduced the noise of the propeller.